Is cerebral microbleed prevalence relevant as a biomarker in amnestic mild cognitive impairment and mild Alzheimer's disease?. Issue 5 (October 2017) - Rabelo, Ana GB; Teixeira, Camila VL; Magalhães, Thamires NC; Carletti-Cassani, Ana Flávia MK; Amato Filho, Augusto CS; Joaquim, Helena PG; Talib, Leda L; Forlenza, Orestes; Ribeiro, Patrícia AO; Secolin, Rodrigo; Lopes-Cendes, Iscia; Cendes, Fernando; et al.
Introduction: The search for a reliable neuroimaging biomarker in Alzheimer's disease is a matter of intense research. The presence of cerebral microbleeds seems to be a potential biomarker. However, it is not clear if the presence of microbleeds has clinical usefulness to differentiate mild Alzheimer's disease and amnestic mild cognitive impairment from normal aging. We aimed to verify if microbleed prevalence differs among three groups: mild Alzheimer's disease, amnestic mild cognitive impairment due to Alzheimer's disease, and normal controls. Moreover, we studied whether microbleeds were associated with apolipoprotein E allele ɛ4 status, cerebrospinal fluid amyloid-beta, total and phosphorylated tau protein levels, vascular factors, and cognition. Methods: Twenty-eight mild Alzheimer's disease patients, 34 with amnestic mild cognitive impairment and 36 cognitively normal elderly subjects underwent: magnetic resonance imaging with a susceptibility-weighted imaging sequence on a 3T scanner, apolipoprotein E genotyping and a full neuropsychological evaluation. Only amnestic mild cognitive impairment and mild Alzheimer's disease underwent cerebrospinal fluid analysis. We compared the groups and verified if microbleeds were predicted by all other variables. Results: Mild Alzheimer's disease presented a higher prevalence of apolipoprotein E allele ɛ4 in relation to amnestic mild cognitive impairment and control group. No significant differences were found between groups when considering microbleed presence. Logistic regression tests failed to find any relationship between microbleeds and the variables. We performed three different regression models using different independent variables: Model 1 - amyloid-beta, phosphorylated tau protein, total tau, apolipoprotein E allele ɛ4 status, age, and sex; Model 2 - vascular risk factors, age, and sex; Model 3 - cognitive scores sex, age, and education. Conclusion: Although microbleeds might be related to the Alzheimer's disease process, their presence is not a good candidate for a neuroimaging biomarker of the disease, especially in its early phases.